MOBILITY OF CORE MELTS DURING EARTHS ACCRETION - Ballhaus C.; Ellis D.J. (My University, 1996)
We have equilibrated carbon-saturated Fe-Ni-Co-S melts in a San-Carlos olivine matrix between 1350 and 1570°C at 2 GPa, to measure the median dihedral angles of metallic core melts in a silicate mantle matrix as a function of temperature and sulfur fugacity. The angles increase from about 68° for the most oxidized monosulfide liquid solutions (metal-sulfur ratio # 0.97), to # 115° for the most reduced metal-rich melts (M/S # 100). Temperature effects are small. These angles preclude that metallic core melts could have segregated efficiently from a crystalline silicate mantle by grain boundary percolation. We suggest that core formation must have occurred from a magma ocean.
Keywords: MELTS; MAGMA OCEANS; CORE; IMMISCIBILITY